2017
DOI: 10.13164/re.2017.1143
|View full text |Cite
|
Sign up to set email alerts
|

TDOA, Frequency and Phase Offsets Estimation Taking Into Account Carrier Phase of Arrival

Abstract: Abstract. This paper deals with estimation of time difference of arrival (TDOA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These tasks are significantly less demanding than estimating classical CSI. For time shift estimation, we propose a noncoherent ML-type algorithm [6] due to the presence of relative phase offsets in the signals [27]. To estimate the residual constant phase offset, we propose a numerically efficient algorithm based on signal correlation.…”
Section: B the Contributions Of The Papermentioning
confidence: 99%
See 2 more Smart Citations
“…These tasks are significantly less demanding than estimating classical CSI. For time shift estimation, we propose a noncoherent ML-type algorithm [6] due to the presence of relative phase offsets in the signals [27]. To estimate the residual constant phase offset, we propose a numerically efficient algorithm based on signal correlation.…”
Section: B the Contributions Of The Papermentioning
confidence: 99%
“…We assume that a m = 1 (∀m), so that the noise variance for a given channel models the propagation attenuation. We recall that a time shift always implies that there is a corresponding phase shift as well, since we deal with RF signals [27].…”
Section: Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 21 ], it has been found that the estimation accuracy based on TDoA could significantly be increased by exploiting the carrier phase of arrival. This suggests that the localization accuracy could also considerably benefit from the carrier phases in spatially coherent settings.…”
Section: Introductionmentioning
confidence: 99%
“…In [9,10], it was shown that the accuracy of TDoA estimation could be significantly increased by exploiting the carrier phase of arrival. Since direct localization is implicitly based on TDoAs, this suggests that the localization accuracy could also benefit significantly from exploiting the carrier phases in spatially-coherent scenarios.…”
Section: Introductionmentioning
confidence: 99%